Thermoregulator protective clothing for young motorcyclist in Selangor / Mohamad Idham Ismail and Shaliza Mohd Shariff - Ismail, Mohamad Idham; Mohd Shariff, Shaliza (Universiti Teknologi MARA, 2021)
Road accidents have become a worldwide issue every year. Malaysia has been ranked at 8th place as a country with high fatalities of road crashes in the Mortality from Road Crashes in 193 Countries Report. Specifically, in Malaysia, fatal accidents cases are mostly caused by motorcyclists in the age group between 16 to 25 years old. To prevent and reduce injuries, motorcyclists need to apply Personal Protective Equipment for safety while riding. Unfortunately, many motorcyclists do not wear PPE due to hot weather with most of them at a young age. The objective of this study is to identify suitable material use and to propose effective protective clothing, especially for young motorcyclists. The researcher applies qualitative research by conducting real case observation and surveys to gather the required data. The protective clothing for young motorcyclists was designed based on the collection of data from respondents. This study will help young motorcyclists to find suitable protective clothing for their safety to reduce the fatalities and injuries cases due to road accidents.